Students' Perception on the Use of TikTok for Learning English - Novitasari Novitasari; Ainul Addinna (Journal of English Language Teaching, 2022)
Currently, there are many media that can be used to learn English independently, one of them is using TikTok social media. This study aims to know and describe students’ perception on the use of TikTok for learning English. The participants of this study were students of the 2021 English Language Education study program who used TikTok to learn English, totaling 21 students filled out questionnaires and 6 students as interviewees. In determining the participants, the researcher used purposive sampling technique. This study used a descriptive method with a qualitative approach. In collecting data, the researcher used observation sheets, questionnaires and interviews. Based on the results of this study, it was found that students have a positive perception of using TikTok to learn English. Learning English by using TikTok can improve students’ English skills. Learning English on TikTok is fun and stress-free. In addition, TikTok has many advantages such as easy to access, varied video content, interesting content and easy to understand, can learn from native speakers, free and many others. However, learning English by using TikTok also has challenges such as internet network problems and costs for internet quota.